Social determinants of domestic violence against suburban women in developing countries: a systematic review - Fatemeh Abdi; Zohreh Mahmoodi; Fatemeh Afsahi; Negin Shaterian; Fatemeh Alsadat Rahnemaei (Korean Society of Obstetrics and Gynecology, 2021)
Objective In addition to the many social, economic, cultural, security, and environmental problems in the metropolitan areas, suburbanization has led to the growth and spread of domestic violence against women, and is still increasing. Different social determinants can play a role in violence against suburban women, so this study was designed to investigate the social determinants of domestic violence in suburban women of developing countries. Methods According to PRISMA guideline, the keywords, which were determined considering MESH, were searched in Google Scholar, MEDLINE, SID, Web of Science, Pubmed, Scopus and Science Direct with the 2009 to 2019 time limit. STROBE checklist was used for evaluating quantitative studies and JBI for qualitative studies. Finally 30 high quality studies were included. Results The prevalence of general domestic violence among women of different ages was reported between 2.3-73.78% in the suburban regions of developing countries. The prevalence of physical, emotional and psychological violence was about 11.54-61.6% and 7.8-84.3%. The prevalence of sexual, economic and the verbal violence was about 0.8-58.8%, 13.7-43.7% and 33.21-86.1%. The most common factors affecting violence against women were the structural factors of early marriage, the husband's addiction to alcohol and drugs. Conclusion General domestic violence and its various types are prevalent in different parts of the world and the factors affecting domestic violence such as age, marriage age, low literacy, husband addiction to alcohol and drugs are all things that can be prevented by special health planning in these areas to improve women's health and thus prevent violence against suburban women.